Ultrasensitive broadband photodetector using electrostatically conjugated MoS2-upconversion nanoparticle nanocomposite. (January 2020) - Ghosh, Sandip; Chiang, Wen Cheng; Fakhri, Muhammad Yusuf; Wu, Chien Ting; Chen, Ruei San; Chattopadhyay, Surojit
Abstract: Hybrid or composite nanomaterials have emerged that demonstrates superior optoelectronic performance over pure nanomaterials that lacks broadband usage, or responsivity, or both, mainly because of the limitation of the collection of photogenerated carriers. We have addressed this problem by using a composite of MoS2 and a multi-photon absorbing lanthanide doped upconversion nanoparticles (UCNPs), that emits in the visible, to make a photodetector (PD) device with ultrahigh broadband responsivity. Single flake MoS2 electrostatically conjugated with UCNPs were used to fabricate the PD device with platinum, and gold contacts. The device was irradiated with UV-to-NIR illumination, at different power density, to study its broadband photosensitivity. Photoresponsivities in excess of 100 A W -1 is easily obtained; a highest responsivity of 1254 A W -1 is reported for 980 nm at 1.0 V bias. An unprecedented normalized gain of 7.12 × 10 − 4  cm 2  V − 1, and Detectivity of 1.05 × 10 15 Jones (@980 nm, 1 V) was obtained which is, to the best of our knowledge, the highest reported till date for this device class. Under vacuum conditions even higher values of these device parameters were obtained, while losing on the response speeds. The photoresponsivity in the nanocomposite followed the trend of the convoluted optical absorption of the individual components. Real application of the PD device was demonstrated using non-laser domestic appliances such as sodium vapour lamp, mobile phone flash light, and air-condition remote controller. Graphical abstract: Electrostatically attached two dimensional molybdenum disulphide with upconversion nanoparticles (MoS2 -UCNPs) is used as a broadband photodetector. The two terminal device (without gate) showed unprecedented normalized gain of 7.12 × 10 −4  cm 2  V −1, and Detectivity of 1.05 × 10 15 Jones (@980 nm, 1 V) which surpassed previous best results, in this class of device, by orders of magnitude. Image 1 Highlights: A novel MoS2 -UCNP hybrid nanocomposite photodetector has been fabricated. The detector had broadband (325–1064 nm) photoresponsivity. The device resulted in highest photoresponsivity, normalized gain, and detectivity, till date, in this class of device.